德州市劳动市场存在问题与展望 = A study on the labor market issues in Dezhou and their policy implications - 盛建军 Sheng, Jianjun (2008)
The study discusses the various problems of surplus labor. The study suggests certain policies that Dezhou city can adopt to improve the present employment situation.